La canzonette : libretto d’une profession de foi - Marsó, Paula (Verbum – Analecta Neolatina, 2013)
La profession de foi du vicaire savoyard [The Profession of Faith of the Savoyard Vicar] is one of Rousseau’s most important reflections on human nature, psychology andmorality, and apart from analyzing the arguments of the profession, questions arise from its semi-detached character about the relation of the Profession to Emile as a whole. The hybrid character of Emile — part a treatise, part a novel — invites an exploration of questions regarding genre, composition, and audience. Rousseau was a successful composer of music, who wrote seven operas as well as music in other forms, and made contributions to music as a theorist. In my opinion, Profession is a musical text, which is based on emotion. The main difficulty of Rousseauian theory of the conscience lies in the reports which it maintains with reason; Jean- Jacques Rousseau challenges this interpretation explicitly: conscience is a feeling.